A Suspicious Cup Disc with High Intraocular Pressure (IOP) and Normal Perimetry: A Rare Self Case Report - Abdiwijoyo, Mario; Nanda Lessi Hafni Eka Putri (HM Publisher, 2024)
Background: Intraocular pressure (IOP) assessment involves evaluating the force exerted by aqueous humor on the internal surface of the anterior eye. Elevated IOP poses a substantial risk for glaucomatous optic neuropathy and is a key modifiable clinical risk factor. This study aims to explore cases of ocular hypertension coupled with optic nerve cupping, suspected to be glaucoma, providing comprehensive details of examination results, diagnosis, and subsequent management. Case presentation: A 23-year-old Asian male underwent an ocular examination, revealing average IOP levels measured using non-contact tonometry. Despite no complaints, consecutive measurements noted 28 mmHg for the right eye and 26 mmHg for the left eye. Initial assessments by a glaucoma specialist indicated open-angle anterior chambers. Optical coherence tomography revealed cup disc ratios of 0.7 to 0.8 for both eyes. Medication (Timol) was prescribed, adjusting with oral citicoline and brinzolamide. The diagnosis evolved to juvenile open-angle glaucoma (JOAG). Visual field testing showed normal results. Discontinuation of treatment led to reclassifying the diagnosis as ocular hypertension and scheduling follow-up OCT examinations for five years. Conclusion: The patient exhibited corneal thickness ≥610 μm, CDR ≥0.7 μm, IOP >25 mmHg, and maintained good visual field conditions. Additional research is essential to understand the correlation between corneal thickness and other eye conditions. Recognizing potential overdiagnosis due to high IOP and large CDR emphasizes the need for meticulous clinical assessment and advanced diagnostic examinations to distinguish physiological and pathological conditions.